EXOMETABOLITES PHYTOSTIMULATION ACTIVITY OF ANTAGONISTIC ACTIVE STRAIN BACILLUS AMYLOLIQUEFACIENS IMV В-7404 - I. В. Драговоз (Mìkrobìologìâ ì Bìotehnologìâ, 2013)
Aim. The research of phytohormonal natural exometabolites by strainantagonist Bacillus amyloliquefaciens IMV B-7404, which determines its phytostimulating activity. Methods. General growth activity, induction of rhizogenesis, specific biological testing, spectrum densitometric thin layer chromatography, high performance liquid chromatography, gas chromatography. Results. Exometabolites phytostimulating activity of B. amyloliquefaciens IMV B-7404 is occurred due presence in its content of three classes of plant hormones-stimulators: auxins, cytokinins and gibberellins. The ability of the strain to synthesize phytohormones-inhibitors such as abscisic acid and ethylene has been shown. Conclusions. The level and range of phytohormons synthesized by strain B. amyloliquefaciens IMV B-7404 support the peculiarities of it’s biology, namely saprobiontic mode of existence. Synthesis of indolyl-3-acetic acid plays an important physiological role in the formation of associative relationships between strains in the plants rhizosphere.